Parallelized and Randomized Adversarial Imitation Learning for Safety-Critical Self-Driving Vehicles - Yun, Won Joon; Shin, Myung Jae; Jung, Soyi; Kwon, Sean; Kim, Joongheon (Journal of Communications and Networks, 2022)
Self-driving cars and autonomous driving research has been receiving considerable attention as major promising prospects in modern artificial intelligence applications. According to the evolution of advanced driver assistance system (ADAS), the design of self-driving vehicle and autonomous driving systems becomes complicated and safety-critical. In general, the intelligent system simultaneously and efficiently activates ADAS functions. Therefore, it is essential to consider reliable ADAS function coordination to control the driving system, safely. In order to deal with this issue, this paper proposes a randomized adversarial imitation learning (RAIL) algorithm. The RAIL is a novel derivative-free imitation learning method for autonomous driving with various ADAS functions coordination; and thus it imitates the operation of decision maker that controls autonomous driving with various ADAS functions. The proposed method is able to train the decision maker that deals with the LIDAR data and controls the autonomous driving in multi-lane complex highway environments. The simulation-based evaluation verifies that the proposed method achieves desired performance.
Keywords: Autonomous driving; Car driving; Decision makers; Deep reinforcement learning; Driving systems; Imitation learning; Random searches; Reinforcement learnings; Self drivings; System functions; Autonomous driving; deep reinforcement learning; imitation learning; random search